in which A1 and refer to a paraxial principal ray calculation for M2 as though it were a primary. Also
Mpr1 = ~(2SPr1 — r2) , in which s*r1 is the pupil shift from M2. But spr1 = 0, so that
From (3.344), this gives
Substituting from (3.343) and (3.345) in (3.341) gives (r1 - 2d1)2(r1 - 2d1 - 2r2)
For the coma-free Schiefspiegler in Z-form, where upr1 and upr2 have the same sign because n1 = - 1:
Y^Sii = (S//)1 + (S//)2 = 0 , giving from (3.342) and (3.346) the condition for freedom from coma in the "axial" image
Was this article helpful?